Assessing the potential of nutrient deficiency for enhancement of biodiesel production in algal resources. Issue 1 (2nd January 2023) - Hasnain, Maria; Abideen, Zainul; Hashmi, Saud; Naz, Shagufta; Munir, Neelma
Abstract: Depleting energy sources result in a growing interest in the conversion of microalgal biofuel to improve economic feasibility. Efficient and cost effective biomass conversion to biofuel demands an increase of carbohydrates and lipid accumulation in algal cells. In the present study, it is measured that concomitant nitrogen, phosphorous and, iron deficiency induces significant physiological and biochemical changes in microalgae Oedogonium sp., Ulothrix sp., Cladophora sp. and Spirogyra sp. by using Response surface methodology as the optimization of growth medium tool. In each of the studied algae species, nutrient deficiency reduced the growth rate of algae as well as protein and chlorophyll of individual cells. On other hand, the biochemical compounds such as carbohydrates were increased up to 0.58 mg/g in Oedogonium sp., 0.56 mg/g in Ulothrix sp., 0.61 mg/g in Cladophora sp., and 0.65 mg/g in Spirogyra sp. as compared to controls. The lipid increased by 75% in Oedogonium sp., 83% in Ulothrix sp., 78% in Cladophora sp., and 73% in Spirogyra sp. lipid content and fatty acid fractions of C16:0, C18:1 and C18:0 of algal species improve under nitrogen, phosphorus and iron deficiency that keeps the fuel properties (EN 14214, ASTM 6751 standard) in the acceptable range important to increase biodiesel quality. The results indicate that nutrient deficiency in algal biomass cultivation can enhance oil and carbohydrates and their subsequent biodiesel production on commercial scale. Highlights: Improve lipid yield of algae under nutrient deficiency is studied for first time Optimization of carbohydrates and lipids of new algal resources was established Algal species could be commercialized for sustainable biodiesel production